Group Exhibition-Facts don’t Speak for themselves-Art on Migration and Borders - Antoniou, Klitsa (My University, 2026)
Facts don’t Speak for themselves-Art on Migration and Borders, The Museum of Forgetting, Skånes konstförening, Malmö, Sweden Curated by Erik Berggren and Kosta Economou